Hadis Yaman Di Tengah Perang Hamas-Israel : Analis Wacana Postingan Hadis Di Media Sosial - Muhammad Nazir Alias; Agus Bahari, Fadhil Achmad; Muhammad Riza Salsabila Bahar; Moh Sirojul Munir (Pustaka Peradaban, 2024)
The use of the Yemeni Hadith on social media amid the Hamas-Israel war raises several issues. This article serves as a response to this phenomenon and addresses various associated problems. As a literature review, it utilizes written data sources, including Yemeni Hadith posts on Instagram and TikTok, Hadith commentaries, and data related to the geopolitical situation in the Middle East. Employing content analysis, the article explores, selects, categorizes, and analyzes documented written data. Using a discourse analysis approach with a constructivist paradigm, it positions Yemeni Hadith posts as something fabricated by their creators with specific motives. Thus, the article aims to answer the question: how has the understanding of the Yemeni Hadith in these posts shifted from authoritative interpretations, and what lies behind these posts? The study's findings reveal that the posts indicate the uploader's incompetence in the fields of Hadith scholarship and Middle Eastern geopolitics, leading to a biased interpretation of the Yemeni Hadith and shaping readers' perspectives to accept interpretations that support the Houthi Yemen group without considering its political context. Additionally, the uploader's motive is rooted in concern for humanitarian issues in Palestine. Penggunaan Hadis Yaman di media sosial di tengah peperangan Hamas-Israel menyisahkan beberapa persoalan. Artikel ini hadir sebagai respon terhadap fenomena tersebut dan menjawab berbagai persoalan yang mengitarinya. Sebagai riset kepustakaan, artikel ini menggunakan data tertulis sebagai sumbernya, berupa unggahan hadis Yaman di Instagram dan TikTok, syarah hadis, dan data-data terkait geo politik Timur Tengah. Menggunakan content analysis, artikel ini mengeksplorasi, menyeleksi, mengategorisasi, dan menganalisa data-data yang terdokumentasi secara tertulis. Menggunakan pendekatan analisa wacana dengan paradigma konstruktivisme, yaitu dengan meletakkan unggahan hadis Yaman sebagai sesuatu yang difabrikasi oleh pembuatnya dengan motif tertentu. Maka artikel ini berusaha menjawab pertanyaan: bagaimana pemahaman hadis Yaman pada unggahan tersebut bergeser dari pemahaman yang otoritatif dan apa yang ada di balik unggahan tersebut? Hasil kajian menemukan bahwa unggahan tersebut menunjukkan inkompetensi pengunggah dalam keilmuan hadis dan geopolitik Timur Tengah, sehingga menjadikan pemaknaan hadis Yaman menjadi bias dan membentuk pola pikir pembaca untuk menerima interpretasi yang mendukung kelompok Houthi Yaman tanpa mempertimbangkan konteks politiknya. Selain itu, motif pengunggah didasari oleh kepedulian terhadap isu kemanusiaan di Palestina.